An investigation into the implementation of in-house versus outsourcing protect management firms in South Africa - Tseki, Ahaka (My University, 2018)
The face of construction is changing globally and with the growing complexity and dynamic nature of construction projects, stakeholders are increasingly under pressure to ensure the successful delivery of projects to their clients. The construction industry has responded to the increasing demands placed on it, with increased specialisation of the services provided by stakeholders, making the management of construction projects increasingly important competencies to ensure that the input of the various contributors on a project is implemented for maximum efficiency. With the increasingly important role construction project management plays in the successful delivery of construction projects, strategic sourcing and organisational boundary decisions have become significant topics of discussion, focusing on the internal organisational issues of project, and the subsequent management of resources and processes. While the fundamental “make or buy” decision has been researched and explored by various researchers in a number of different fields. Research into the boundary decision in the field of construction project management services, particularly the factors influencing large property development firms in making the boundary decision, has been found incomplete and this research aims to add to this body of knowledge. Therefore, the purpose of this research was to explore the factors/ considerations that influence clients, specifically large property development firms, in making the choice between retaining project management services in-house sourcing the same services externally from the market. To investigate the above, a qualitative research strategy was applied using two case studies. Data was collected using semi-structured interviews as the primary method and using a questionnaire survey as a supplementary, secondary method. Where respondents both the interviews and questionnaire survey were selected using a non-probabilistic purposeful sampling strategy. The research found trust and ognanisational capabilities were the two most important factors for large property development firms when making this boundary decision. Where trust and ognanisational capabilities were found to have an inversely proportional and directly proportional relationship respectively with the likelihood of a large property development firm retaining construction project management services in-house, rather than outsourcing the same services. It is anticipated that the results of the research will provide a better understanding of not only the advantages and disadvantages of implementing either sourcing option but perhaps more importantly, insight into the reasons why either sourcing option chosen.
A research report submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Building, Johannesburg 2018
Keywords: Project management; Construction industry